Neuron with well-designed ionic system - Takayoshi Tsubo (Biophysics and Physicobiology)
Neurons have an ionic system with several types of ion pumps and ion channels on their membranes. Each ion pump creates a specific difference in ion concentration inside and outside the neuron, and the energy resulting from this difference in concentration is maintained inside the neuron as a resting potential. Each ion channel senses the necessary situation, opens the channel, and allows the corresponding ion to pass through to perform its corresponding role. This ionic system realizes important functions such as (i) fast conduction of action potentials, (ii) achieving synaptic integration in response to several inputs with a time lag, and (iii) the information processing functions by neural circuits. However, the mechanisms by which these functions are realized have remained unclear. Therefore, based on the reports on various highly polymeric ion pumps, ion channels, cell membranes, and other components that have been elucidated so far, author analyzed how this ionic system can realize the above important functions from an electrical circuit designer point of view. As a result of a series of analyses, it was found that neurons realize each function by making full use of high-density packaging technology based on basic electrical principles and making maximum use of the extremely high dielectric properties of the ionic fluid of neurons. In other words, neuron looks to equip well designed ionic system which is the collaboration by designers of proteins and membranes that perform advanced functions and designers of electrical circuits that utilize them to achieve important functions electrically.